The NIH BD2K center for big data in translational genomics. (14th July 2015) - Paten, Benedict; Diekhans, Mark; Druker, Brian J; Friend, Stephen; Guinney, Justin; Gassner, Nadine; Guttman, Mitchell; James Kent, W; Mantey, Patrick; Margolin, Adam A; Massie, Matt; Novak, Adam M; et al.
Abstract: The world's genomics data will never be stored in a single repository – rather, it will be distributed among many sites in many countries. No one site will have enough data to explain genotype to phenotype relationships in rare diseases; therefore, sites must share data. To accomplish this, the genetics community must forge common standards and protocols to make sharing and computing data among many sites a seamless activity. Through the Global Alliance for Genomics and Health, we are pioneering the development of shared application programming interfaces (APIs) to connect the world's genome repositories. In parallel, we are developing an open source software stack (ADAM) that uses these APIs. This combination will create a cohesive genome informatics ecosystem. Using containers, we are facilitating the deployment of this software in a diverse array of environments. Through benchmarking efforts and big data driver projects, we are ensuring ADAM's performance and utility.